বাংলাদেশের ভূমিব্যবস্থা - ইসলাম,কাবেদুল 1964- (ঢাকা : মাওলা ব্রাদার্স, 1999)
On the land use in Bangladesh.
Includes bibliographical references (p. [263]-280).
In Bengali; includes passages in English.
Keywords: Land use -- Bangladesh